Islamic Worldview : Tinjauan Pemikiran Syech Muhammad Naquib Al-Attas dan Budaya Keilmuan Dalam Islam - Melinda Rahmawati; Fitri Nur Aini; Yustiara Nuraini; Bagus Muhammad Mahdi (NALAR, 2020)
The purpose of this article is to know more about the thoughts of Syech Muhammad Naquib Al-Attas about Islamic Worldview and its influence in Islamic scientific culture. The starting point for the advancement of Islamic scientific views was during the Daulay Abbasiyah era. While at the same time Europe was facing an intellectual crisis due to various restrictions imposed by the church clergy. The scientific outlook developed by Muslim scholars inspired European scholars to move forward towards the Renaissance. However, since the Rennaissance of scientific developments in the Islamic world has declined until now. The number of Muslim scholars is now beginning to be few and almost no successor. Method that used in article is qualitative explanation method with generative approach, who gave identification in detail about Islamic Worldview in the view of Syech Muhammad Naquib Al-Attas and its relation to the re-development in Islamic perspective. This article used literature study analysis by comparing and studying several literacies such as textbooks, scientific journals and others related to Syech Muhammad Naquib Al-Attas's thoughts on Islamic Worldview. The thought of Syech Muhammad Naquib Al-Attas is what ignited the awareness of Muslims to revive scientific culture in the Islamic view. The result of this article is he knew knowledge of Syech Muhammad Naquib Al-Attas's view on Islamic Worldview and its influence in Islamic scientific culture. The conclusion of this article is that Islamic Worldview as a manifestation of the scientific culture of Muslims must be developed. The truth that is believed by Muslims is the truth of the existence of God who created this universe. Belief in the existence of God as creator prevents us from doubting the essence of life.Keyword : Islamic Worldview; Thought; Syech Muhammad Naquib Al-Attas